The Influence of Human Resource Competence and Employee Training on Service Performance: The Intervening Role of Work Enthusiasm Among Sub-District Offices Employee in Serang City - Eti Mumtahinah; Sutisna Sutisna; Munawaroh Munawaroh (Economics and Digital Business Review, 2026)
This research is motivated by the suboptimal quality of public services which requires increasing the competence of civil servants, training effectiveness, and strengthening work enthusiasm in order to realize professional, responsive, and quality services. This study aims to analyze the influence of human resource competency and employee training on service performance through work enthusiasm as an intervening variable on sub-district employees in Serang City. This study employed a quantitative approach with a survey method. Sample on this research were sub-district employees directly involved in public services are 129. Data collection was conducted through questionnaires, while data analysis used Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test direct and indirect relationships between research variables. The results of the study indicate that human resource competency and employee training have a positive and significant impact on service performance. Human resource competency and employee training have also been shown to increase work morale, which in turn positively contributes to improved service performance. Furthermore, work morale has been shown to act as an intervening variable, strengthening the influence of human resource competency and employee training on service performance. This study concludes that improving the quality of public services requires developing human resource competencies, providing ongoing training, and strengthening employee morale. Therefore, local governments need to integrate these three aspects into human resource management to improve the effectiveness of public services and meet public expectations.